2020
DOI: 10.3390/s20092524
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral LIF-Based Standoff Detection System for the Classification of CBE Hazards by Spectral and Temporal Features

Abstract: Laser-induced fluorescence (LIF) is a well-established technique for monitoring chemical processes and for the standoff detection of biological substances because of its simple technical implementation and high sensitivity. Frequently, standoff LIF spectra from large molecules and bio-agents are only slightly structured and a gain of deeper information, such as classification, let alone identification, might become challenging. Improving the LIF technology by recording spectral and additionally time-resolved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A multi-wavelength sub-nanosecond laser source was used to acquire spectral and time-resolved data from a standoff distance of 3.5 m from seven different bacterial species and six types of oil. Classification performed with a decision tree algorithm showed that accuracy was increased from 86% for spectral data only to more than 92% when combined with time-resolved data [49].…”
Section: Excitation Light Sourcesmentioning
confidence: 99%
“…A multi-wavelength sub-nanosecond laser source was used to acquire spectral and time-resolved data from a standoff distance of 3.5 m from seven different bacterial species and six types of oil. Classification performed with a decision tree algorithm showed that accuracy was increased from 86% for spectral data only to more than 92% when combined with time-resolved data [49].…”
Section: Excitation Light Sourcesmentioning
confidence: 99%
“…In addition, the specificity of the Rayleigh‐LIF‐LiDAR platform could be enhanced by using multiple channels of resolution for acquiring the LIF spectra (Kaye et al ., 2005; Ruske et al ., 2017). The specificity of the hyphenated LiDAR platform could further be enhanced by acquiring data on fluorescence lifetimes (time‐resolved LIF data) of the viruses and other aerosol particles, as was recently demonstrated for detection, classification and identification of some CBE agents (Fellner et al ., 2020).…”
Section: Lif‐lidar For Viral Surveillance: What Will It Take?mentioning
confidence: 99%
“…Even though some studies have presented < 10 m and > 10 m as short and long stand‐off range, respectively (Bogue, 2018), this review adopts the detection distances < 20 m, 20–100 m and > 100 m as short, medium and long stand‐off detection range, respectively, in consonance with many other reports (Sedlacek et al ., 2002; Huestis et al ., 2010; Babichenko et al ., 2018; Fellner et al ., 2020). Stand‐off detection methods are suitable for operations in high risk and harsh environments, as they could provide information about CBE hazards in real‐time from safe distances of several centimetres to up to a kilometre (Jonsson et al ., 2009; Babichenko et al ., 2018; Fellner et al ., 2020). Based on these advantages, stand‐off detection will be an ideal approach for viruses, which can be highly contagious and dangerous.…”
Section: Introductionmentioning
confidence: 99%
“…High classification performances (more than 90%) have been obtained in the most of applications, remote sensing included. On the contrary, no results and detailed investigations about the concentration measurements and classification of mixture samples are available in the literature [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%